Education and philanthropy in the Middle East and North Africa (2019)
In North America and Europe, philanthropic foundations established by individuals, families and corporations have been operating in the education sector for over one hundred years (Arnove, 1984; Berman, 1983; Eikenberry & Nickel, 2006; Zunz, 2014). Globally, however, the last two decades have seen a significant increase in the level of involvement of philanthropic organisations in the education sector in most regions of the world, including the Middle East and North Africa (MENA) (Srivastava & Oh, 2010; Zunz, 2014). The growth in giving in the MENA region appears to have been driven by two key factors: first, a strong religious or cultural imperative to give back (Farouky, 2016; Ibrahim, 2008) and second, growing levels of personal and state wealth across the MENA region that have created a greater capacity for philanthropic giving (Knight & Ribeiro, 2017).